KUALITAS PEROLEHAN HASIL BELAJAR MATEMATIKA DENGAN MODEL KOOPERATIF TIPE POWER OF TWO DI SMP - Nuralam; Nailul Audhar (Program Studi Pendidikan Matematika, Universitas Bina Bangsa Getsempena, 2018)
Students' mathematics learning outcomes were still not optimally. This condition is due to several aspects, including teacher's more active learning activities than students. One alternative solution so that optimal mathematics learning outcomes are taught with the power of two cooperative learning model. The purpose of this study is to describe: (1) the mathematics learning outcomes through by the power of two type of cooperative learning model is higher than taught through conventional learning models; (2) student responses to learning activities. This research uses a quasi-experimental design. The population is students of SMPN 1 Aceh Besar grade VII and the sample was cluster random sampling. Data collected through tests of mathematics learning outcomes and response questionnaires. Data analysis techniques used descriptive and inferential. The results of the research with t-test statistics obtained tcount = 3,8 and ttable = 2,1 then tcount> ttable so that Ha accepted reject Ho and the student response mean score was 3,3 and classical learning completeness was 90,5%. Therefore, it was concluded that (1) the mathematics learning outcomes through by the power of two type of cooperative learning model of were higher than those taught with conventional learning models. (2) students' responses to learning activities in the very positive category. Abstrak Hasil belajar matematika siswa masih kurang optimal. Kondisi ini karena beberapa aspek, diantaranya kegiatan pembelajaran lebih aktif guru daripada siswa. Salah satu alternatif penyelesaian agar hasil belajar matematika optimal dibelajarkan dengan model pembelajaran kooperatif tipe power of two. Tujuan penelitian untuk mengetahui: (1) hasil belajar matematika yang dibelajarkandengan model pembelajaran kooperatif tipe power of two lebih tinggi daripada model pembelajaran konvensional; (2) respon siswa terhadap aktivitas pembelajaran. Penelitian ini menggunakan desain eksperimen semu. Populasi seluruh siswa kelas VII SMPN 1 Aceh Besar dan sampel diambil secaracluster random sampling. Data dikumpulkan melalui tes hasil belajar matematikadan angket respon. Data dianalisis menggunakan teknik deskriptif dan inferensial Hasil penelitian dengan statistik uji-t diperoleh thitung= 3,8 dan ttabel = 2,1 maka thitung ttabelsehingga terima Ha tolak Ho dan respon siswa skor rerata yaitu 3,3 dan ketuntasan belajar secara klasikal sebesar 90,5%. Oleh karena itu disimpulkan bahwa (1) hasil belajar matematikayang dibelajarkan dengan model pembelajaran kooperatif tipepower of twolebih tinggi daripada dibelajarkan dengan model pembelajaran konvensional. (2) respon siswa terhadap aktivitas pembelajaran dalam kategori sangat positif. Kata kunci: Hasil belajar matematika, model pembelajaran kooperatif, tipe power of two